Effect of thermal treatment on selected bioactive compounds and physicochemical properties of a blackberry-soy-flaxseed beverage - Bonilla Soto, Ana Irene (2024)
Three prototypes of a blackberry-soy-flaxseed beverage were formulated and processed by pasteurization (71.1 ◦C, 3 s) or commercial sterilization (heating to 87 ◦C followed by immediate hot-fill). The effects of heat exposure on selected bioactive compounds (total phenolics, ellagitannins, anthocyanins, isoflavones and lignans) and physicochemical properties (pH, ◦Brix, turbidity, viscosity and color) were evaluated. Bioactive compounds were quantified by HPLC-DAD analytical methods. No significant changes (p > 0.05) were observed in the contents of total phenolic compounds, ellagitannins, cyanidin-3-glucoside, isoflavones (daidzein and genistein), or lignans, regardless of the heat regime applied or the beverage formulation. The pH and soluble solids were similar among the three beverages and did not change after heat treatments. The content of cyanidin-3-malonylglucoside, a polyphenol, significantly decreased (p < 0.05) by 35–45% with the hot-fill process in all beverage prototypes. Turbidity was not significantly affected by the type of heat treatment, but the viscosity of the hotfilled beverages was significantly higher (p < 0.05) than that of the pasteurized and non-pasteurized prototypes. No significant differences (p < 0.05) in color parameters L*, a*, and b* were observed. Total color difference (DE*) values indicated differences in perceivable color among samples of the same beverage exposed to the heat processing regimes. DE* values for prototype 1 processed by pasteurization and commercial sterilization were distinct from non-pasteurized beverage. DE* values for prototypes 2 and 3 processed by pasteurization were distinct from those of the non-pasteurized beverage. Pasteurization allowed higher retention of bioactive compounds and had a lower impact on the physicochemical properties of the blackberry-soy-flaxseed beverage.